Determination of Cardiothoracic Ratio (CTR) and Image Contrast in Chest Radiographs Using Variations in Focus-Film Distance (FFD) - Fickry Haikal; Sri Dewi Astuty; Sultan Hamjar; Syamsir Dewang; Bannu Bannu; Arfinna Arfinna; Ayu Hardianti Pratiwi; Ajeng Anggreny Ibrahim (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
Posteroanterior (PA) chest radiography is generally recommended at a focus-to-film distance (FFD) of 180 cm to minimize magnification of the cardiac silhouette, which may affect assessment of cardiomegaly. However, shorter FFDs are sometimes unavoidable because of room constraints or patient-related conditions. This study aimed to evaluate cardiothoracic ratio (CTR) values obtained at different FFDs and assess cardiac image quality using the contrast-to-noise ratio (CNR) to determine the visibility of the right and left cardiac borders. A descriptive observational study with a post-test-only design was conducted using 70 digital PA chest radiographs from male patients aged 17–22 years. The images were divided into seven FFD groups ranging from 120 to 180 cm, with 10 independent samples per group. CTR and CNR were quantitatively measured using ImageJ software. All radiographs demonstrated CTR values below 50% across the investigated FFDs, indicating no radiographic evidence of cardiomegaly. The highest mean CNR values were observed at FFDs of 140 cm (64.458), 150 cm (58.639), and 180 cm (50.758). Statistical analysis revealed no significant differences in CTR (p = 0.515) or CNR (p = 0.141) among the FFD groups. The observed fluctuations in CTR and CNR were likely attributable to inter-individual anatomical variation rather than FFD-related magnification. Differences in chest geometry and tissue attenuation, particularly variations in thoracic thickness and density, may have contributed substantially to the observed measurements. These findings suggest that, within the investigated range, FFD variations from 120 to 180 cm did not significantly affect CTR or CNR in young adult male subjects.